Comparison of Malassezia Colonization on Atopic Dermatitis Patients and Control - Ardsari Azminingrum; Iskandar Zulkarnain; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Atopic dermatitis (AD) is a chronic skin disease that often occurs in infancy and children. Skin barrier defect in atopic dermatitis causes the skin susceptible to bacterial, fungal, and viral infection. Antifungal therapy can improve atopic dermatitis by reducing the number of Malassezia colonization on the skin. Purpose: To compare Malassezia colonization of children with AD and non-AD children in Dermato-venereology Outpatient Clinic in Dr. Soetomo general hospital Surabaya. Methods: This was an analitic observational study, 25 atopic dermatitis and 25 non-atopic children (controls) that qualify inclusion and exclusion criteria were eligibled. Skin specimens were obtained by skin scraping and then planted in the culture medium ChromAgar Malassezia. Results: Positive culture of Malassezia in AD group was fewer than the control group, while the average number colony of Malassezia sp.in atopic dermatitis was higher than the control group; but statistic analysis showed the difference was not significant (p>0.05), except in seborrheic area. Conclusions: The average number colony of Malassezia sp. was higher in AD patient than control group in this study. Statistic analysis showed the difference was not significant, except in seborrheic area. This results differ with previous study can be possible due to the difference of using culture medium and methods of skin specimen collection, as well as the influence of tropical climate that occurred in Indonesia.